High-performance composite current collector and preparation method thereof

By adding PET grafted polyaniline copolymer nanofibers and reduced graphene oxide to the PET film, and using plasma treatment, magnetron sputtering and electroplating processes, a high-performance composite liquid collector was prepared, which solved the problems of low conductivity, poor cycle stability and poor flame retardancy of the current collector, and achieved higher comprehensive performance and safety.

CN119581567AActive Publication Date: 2025-03-07SHIPU LISTED POLYMER NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411752378.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing current collectors have problems such as low conductivity, poor cycle stability and poor flame retardancy, resulting in poor overall performance.

Method used

A high-performance composite fluid collector is employed, which includes a base film and a metal layer on at least one side of the base film. By adding PET grafted polyaniline copolymer nanofibers and reduced graphene oxide to the PET film, combined with plasma treatment, magnetron sputtering and electroplating processes, a composite fluid with high conductivity, good mechanical properties and excellent flame retardancy were prepared.

Benefits of technology

The current collector's conductivity, cycle stability and flame retardancy are improved, significantly improving its comprehensive performance, allowing it to exhibit higher energy density and better safety in battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of battery current collectors, and discloses a high-performance composite current collector, which comprises a base film and a metal layer on at least one side of the base film, the base film is prepared from the following raw material components in parts by weight: 65 to 95 parts of PET (Polyethylene Terephthalate), 2 to 25 parts of PET grafted polyaniline, 0.2 to 5 parts of graphene oxide, 0.1 to 5 parts of a coupling agent, 1 to 5 parts of maleic anhydride grafted PET and 1 to 5 parts of imide modified PET. By adopting the composite current collector provided by the invention, the balance, the thermal decomposition temperature and the flame-retardant capability of the current collector can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery current collectors, and in particular to a high-performance composite current collector and a preparation method thereof. Background Art

[0002] At present, current collectors play an important role in energy storage devices such as batteries and supercapacitors. Its function is to carry the positive and negative active materials and collect the battery active materials to generate a large output current. Traditional current collectors usually choose aluminum foil and copper foil as positive and negative electrode materials. Taking the negative electrode current collector as an example, the core technology is mainly reflected in the thickness of lithium battery copper foil, overall conductivity, tensile strength, elongation, roughness, oxidation resistance, safety and other technical indicators. In terms of energy density, the thinner the lithium battery copper foil, the greater the effect on improving the energy density of the battery. Compared with traditional current collectors, composite current collectors have the advantages of good mechanical properties, low manufacturing cost, and strong compatibility, and batteries using composite current collectors also have a good improvement in energy density. However, the existing current collectors have certain performance limitations, such as low conductivity, poor cycle stability, poor flame retardancy, etc., resulting in poor overall performance. Based on this, it is particularly necessary to develop a current collector material with excellent comprehensive performance. Summary of the invention

[0003] Technical problems solved by the present invention:

[0004] It is used to solve the technical problems of low conductivity, poor cycle stability and poor flame retardancy of existing current collectors.

[0005] The technical solution adopted by the present invention is:

[0006] In view of the above technical problems, the purpose of the present invention is to provide a high-performance composite current collector and a preparation method thereof. Based on this, the specific implementation scheme is as follows:

[0007] A high-performance composite current collector includes a base film and a metal layer on at least one side of the base film; a preparation method thereof includes the following steps:

[0008] S1. Blending the components of the raw materials to obtain a mixture;

[0009] The raw material components are specifically: 65-95 parts of PET, 2-25 parts of PET grafted polyaniline, 0.2-5 parts of graphene oxide, 0.1-5 parts of coupling agent, 1-5 parts of maleic anhydride grafted PET, and 1-5 parts of imide modified PET.

[0010] in,

[0011] PET: weight average molecular weight is 15000-35000, polydispersity coefficient is less than 2.5;

[0012] PET grafted polyaniline: The morphology is nanofibers with a diameter of 10nm to 40nm and a length of 80nm to 500nm;

[0013] PET grafted polyaniline: The weight average molecular weight of PET in PET grafted polyaniline is 5000-15000;

[0014] Reduced graphene oxide: The morphology is nanosheets, with a length and width of 50nm to 100nm;

[0015] The coupling agent includes N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane;

[0016] The molecular structure of maleic anhydride grafted PET is shown in (I):

[0017]

[0018] n = 10 to 50;

[0019] The molecular results of imide-modified PET are shown in (II):

[0020]

[0021] m=5~30.

[0022] S2 extrudes, casts, casts, and stretches the mixture to obtain a base film;

[0023] The extrusion adopts a twin-screw extruder, which is equipped with three exhaust ports and three vacuum systems. The extruder has 8 to 12 heating zones in total, and the temperature from the feed port to the die is 120 to 315° C. The die of the cast sheet is a hanger type, and the die temperature is 250 to 300° C. Stretching includes transverse stretching and longitudinal stretching.

[0024] The base film thickness is 1 to 15 μm.

[0025] S3 processes both sides of the base film so that a metal layer is generated on the surface of the base film.

[0026] Among them, the processing includes plasma treatment, magnetron sputtering and electroplating processes.

[0027] The plasma treatment is Ar / O2 low-pressure plasma treatment; the treatment time is 30 to 200 seconds; the pressure is less than 50 Pa; the surface energy of the film after the plasma treatment is 40 to 60 dyne / cm.

[0028] The magnetron sputtering is vacuum magnetron sputtering; the argon gas pressure is 0.5-25 Pa; the cathode anode voltage is 1-8 KV; the thickness of the metal layer obtained by magnetron sputtering is 5-150 nm.

[0029] Electroplating process: The pH value of the electroplating solution is 4 to 6.5; the electroplating solution includes 50 to 350 g / L of copper sulfate, 0.1 to 35 mg / L of 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 20 to 200 mg / L of chloride ions, and 0.2 to 30 mg / L of hexadecyltrimethylammonium bromide; the electroplating voltage is 10 to 30 V; the electroplating current is 0.5 to 20 A / dm 2 ; The thickness of the metal layer obtained by electroplating is 0.2 to 10 μm.

[0030] The technical mechanism and beneficial effects adopted by the present invention are as follows:

[0031] (1) When preparing the PET film, PET grafted polyaniline copolymer nanofibers and reduced graphene oxide with intrinsic conductive function are added, so that the PET film itself has both good conductivity and mechanical properties;

[0032] (2) Due to the good flame retardancy of PET grafted polyaniline copolymer and reduced graphene oxide, their addition can improve the flame retardancy of the current collector and further improve safety;

[0033] (3) The relatively low molecular weight of PET grafted polyaniline copolymer nanofibers makes the fibers extremely compatible with PET resin, which is conducive to the uniform dispersion of the fibers in the PET resin.

[0034] (4) The added maleic anhydride grafted PET copolymer can be used as a compatibilizer due to its PET molecular weight, which can greatly improve the compatibility of the various components of the raw materials, facilitate the uniform dispersion of the various components, and ensure the balance of the collector performance.

[0035] (5) The imide-modified PET copolymer has an imide-exchange structure with good thermal stability and flame retardancy, which can greatly improve the thermal decomposition temperature and flame retardancy of the current collector.

[0036] (6) The surface of the PET film is treated with plasma. At the same time, due to the presence of reduced graphene oxide, the hydroxyl, carboxyl, epoxy, carbonyl, etc. in the graphene oxide are distributed on the surface of the PET film, which increases the degree of surface activation of the PET film, is conducive to the close connection of the nano-scale copper layer during magnetron sputtering, and can improve the long-term stability of the composite current collector. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0038] Example 1

[0039] 85 parts of PET resin, 7 parts of PET grafted polyaniline copolymer nanofibers, 1.5 parts of reduced graphene oxide nanosheets, 0.5 parts of coupling agent (N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane), 3 parts of maleic anhydride grafted PET copolymer, and 3 parts of imide modified PET copolymer are mixed evenly in a high-speed mixer; the PET resin has a weight average molecular weight of 25000 and a polydispersity coefficient of 2.25; the PET grafted polyaniline copolymer nanofiber has a diameter of 25nm and a length of 150nm; the length and width of the reduced graphene oxide nanosheets are both 50nm to 100nm.

[0040] The evenly mixed materials are melt-extruded into thick sheets, cast sheets and cast sheets through an extruder, and a composite base film is obtained through longitudinal and transverse stretching; the extruder has a total of 10 heating zones, and the temperatures from the feed port to the die are 150°C, 200°C, 250°C, 290°C, 290°C, 290°C, 290°C, 290°C, 290°C, 290°C, and 290°C, respectively; the die head of the cast sheet is a hanger-type die head, and the die head temperature is 280°C. The thickness of the obtained base film is 3μm.

[0041] Both sides of the composite base film are subjected to plasma treatment, magnetron sputtering and electroplating processes to generate a conductive metal layer on the surface. The plasma treatment time is 80s, the pressure is 20Pa, and the surface energy of the film after treatment is 54dyne / cm. During magnetron sputtering, the argon gas pressure is 20Pa, and the cathode anode voltage is 6kV. The metal layer obtained by magnetron sputtering is 80nm thick copper. The solution of the electroplating process has a pH value of 6.0; the electroplating solution includes 280g / L of copper sulfate, 25mg / L of 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 120mg / L of chloride ions, and 10mg / L of hexadecyltrimethylammonium bromide; the electroplating voltage is 18V and the current is 12A / dm 2 The thickness of the electroplated copper on both sides was 1.5 μm.

[0042] Example 2

[0043] 86 parts of PET resin, 9 parts of PET grafted polyaniline copolymer nanofibers, 1 part of reduced graphene oxide nanosheets, 0.5 parts of coupling agent (N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane), 1.5 parts of maleic anhydride grafted PET copolymer, and 3 parts of imide modified PET copolymer are mixed evenly in a high-speed mixer; the PET resin has a weight average molecular weight of 25,000 and a polydispersity coefficient of 2.3; the PET grafted polyaniline copolymer nanofibers have a diameter of 35 nm and a length of 180 nm; the length and width of the reduced graphene oxide nanosheets are both 50 nm to 100 nm.

[0044] The evenly mixed materials are melt-extruded into thick sheets, cast sheets and cast sheets through an extruder, and a composite base film is obtained through longitudinal and transverse stretching; the extruder has a total of 10 heating zones, and the temperatures from the feed port to the die are 120°C, 170°C, 220°C, 270°C, 300°C, 300°C, 300°C, 300°C, 300°C, and 300°C, respectively; the die head of the cast sheet is a hanger-type die head, and the die head temperature is 290°C. The obtained base film has a thickness of 1.5 μm.

[0045] Both sides of the composite base film are subjected to plasma treatment, magnetron sputtering and electroplating processes to generate a conductive metal layer on the surface. The plasma treatment time is 50s, the pressure is 15Pa, and the surface energy of the film after treatment is 56dyne / cm. During magnetron sputtering, the argon gas pressure is 15pa, and the cathode anode voltage is 5.5kv. The metal layer obtained by magnetron sputtering is 50nm thick copper. The solution of the electroplating process has a pH value of 6.0; the electroplating solution includes 300g / L of copper sulfate, 15mg / L of 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 180mg / L of chloride ions, and 20mg / L of hexadecyltrimethylammonium bromide; the electroplating voltage is 22V and the current is 15A / dm 2 The thickness of the electroplated copper on both sides was 1.8 μm.

[0046] Example 3

[0047] 88 parts of PET resin, 6 parts of PET grafted polyaniline copolymer nanofibers, 1.5 parts of reduced graphene oxide nanosheets, 0.5 parts of coupling agent (N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane), 1 part of maleic anhydride grafted PET copolymer, and 3 parts of imide modified PET copolymer are mixed evenly in a high-speed mixer; the weight average molecular weight of the PET resin is 25000, and the polydispersity coefficient is 2.2; the PET grafted polyaniline copolymer nanofibers have a diameter of 20nm and a length of 150nm; the length and width of the reduced graphene oxide nanosheets are both 50nm to 100nm.

[0048] The uniformly mixed materials are melt-extruded into thick sheets, cast sheets, and cast sheets through an extruder, and then stretched longitudinally and transversely to obtain a composite base film; the extruder has a total of 10 heating zones, and the temperatures from the feed port to the die are 180°C, 260°C, 285°C, 285°C, 285°C, 285°C, 285°C, 285°C, 285°C, 285°C, 285°C, and 285°C, respectively. The die head of the cast sheet is a hanger-type die head, and the die head temperature is 280°C. The obtained base film has a thickness of 1.0 μm.

[0049] Both sides of the composite base film are subjected to plasma treatment, magnetron sputtering and electroplating processes to generate a conductive metal layer on the surface. The plasma treatment time is 40s, the pressure is 15Pa, and the surface energy of the film after treatment is 52dyne / cm. During magnetron sputtering, the argon gas pressure is 15Pa, and the cathode anode voltage is 6kV. The metal layer obtained by magnetron sputtering is 60nm thick copper. The solution of the electroplating process has a pH value of 6.0; the electroplating solution includes 200g / L of copper sulfate, 8mg / L of 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 120mg / L of chloride ions, and 10mg / L of hexadecyltrimethylammonium bromide; the electroplating voltage is 13V and the current is 8A / dm 2 The thickness of the electroplated copper on both sides was 0.5 μm.

[0050] Test example

[0051] The samples prepared in Examples 1-3 were tested, the tensile properties were in accordance with GB / T1040.1.2018, the flame retardancy was in accordance with UL94 standard, and the cycle test was carried out: a soft pack battery was prepared, the charge and discharge conditions were 0.33C / 1C, and the temperature was 25°. The results are shown in Table 1.

[0052] Table 1

[0053]

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-performance composite current collector, characterized in that: comprising a base film and a metal layer on at least one side of the base film; The raw material components of the base film include 65-95 parts of PET, 2-25 parts of PET grafted polyaniline, 0.2-5 parts of graphene oxide, 0.1-5 parts of coupling agent, 1-5 parts of maleic anhydride grafted PET, and 1-5 parts of imide modified PET, by weight.

2. The high performance composite current collector according to claim 1, characterized in that: Each component of the raw material includes at least one of the characteristics (1) to (5): (1) PET: weight average molecular weight is 15000-35000, and polydispersity coefficient is less than 2.5; (2) PET grafted polyaniline: the morphology is nanofibers with a diameter of 10nm to 40nm and a length of 80nm to 500nm; (3) PET grafted polyaniline: The weight average molecular weight of PET in PET grafted polyaniline is 5000-15000; (4) Reduced graphene oxide: The morphology is nanosheets, with a length and width of 50nm to 100nm; (5) The coupling agent includes N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

3. The high performance composite current collector according to claim 1 or 2, characterized in that: Each component of the raw material includes at least one of the characteristics (6) to (7): (6) The molecular structure of maleic anhydride grafted PET is shown in (I): n=10~50; (7) The molecular results of imide-modified PET are shown in (II): m=5~30。 4. The method for preparing a high-performance composite current collector according to any one of claims 1 to 3, characterized in that: The steps include: S1. Blending the components of the raw materials to obtain a mixture; S2 extrudes, casts, casts, and stretches the mixture to obtain a base film; S3 processes both sides of the base film so that a metal layer is generated on the surface of the base film.

5. The method for preparing a high-performance composite current collector according to claim 4, characterized in that: In S2, a twin-screw extruder is used for extrusion, and is provided with three exhaust ports and three vacuum systems. The extruder has a total of 8 to 12 heating zones, and the temperature from the feed port to the die is 120 to 315°C. The die of the cast sheet is a hanger type, and the die temperature is 250 to 300°C.

6. The method for preparing a high-performance composite current collector according to claim 4, characterized in that: In S2, the base film thickness is 1 to 15 μm.

7. The method for preparing a high-performance composite current collector according to claim 4, characterized in that: In S3, the processing includes plasma treatment, magnetron sputtering and electroplating processes.

8. The method for preparing a high-performance composite current collector according to claim 7, characterized in that: The plasma treatment includes at least one of features (1) to (4): (1) The plasma treatment is Ar / O2 plasma treatment; (2) The processing time is 30 to 200 seconds; (3) Pressure <50Pa; (4) The surface energy of the film after plasma treatment is 40-60 dyne / cm.

9. The method for preparing a high-performance composite current collector according to claim 7, characterized in that: Magnetron sputtering includes at least one of the following features (1) to (4): (1) Magnetron sputtering is vacuum magnetron sputtering; (2) Argon gas pressure is 0.5~25pa; (3) Cathode anode voltage is 1~8kV; (4) The thickness of the metal layer obtained by magnetron sputtering is 5 to 150 nm.

10. The method for preparing a high-performance composite current collector according to claim 7, characterized in that: The electroplating process includes at least one of the following features (1) to (5): (1) The pH value of the plating solution is 4 to 6.5; (2) The plating solution comprises 50 to 350 g / L of copper sulfate, 0.1 to 35 mg / L of 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 20 to 200 mg / L of chloride ions, and 0.2 to 30 mg / L of hexadecyltrimethylammonium bromide; (3) The electroplating voltage is 10 to 30 V; (4) The electroplating current is 0.5 to 20 A / dm 2 ; (5) The thickness of the metal layer obtained by electroplating is 0.2 to 10 μm.

Citation Information

Patent Citations

  • Composite current collector for negative electrode of lithium battery as well as preparation method and application of composite current collector

    CN115275213A

  • Multilayer composite current collector

    CN116314841A

  • Graphene modified PET (Polyethylene Terephthalate) film for high-strength heat-resistant lithium battery current collector and preparation method of graphene modified PET film

    CN116694033A

  • High-strength base membrane for composite current collector and preparation method of high-strength base membrane

    CN118772476A

  • Composite current collector and manufacturing method therefor, and electrochemical device

    WO2022141069A1